Avaliação da via autofágica no parasito Schistosoma mansoni: uma abordagem por bioinformática e microscopia - Bastos, Julliane Almeida (2019)
The parasite Schistosoma mansoni is the cause of schistosomiasis in Brazil. Currently the drug Praziquantel (PZQ) is the schistosomicide of choice used in the treatment of the disease, and the search for new effective drugs against the parasite is necessary, given the reports about the presence of lines less sensitive to PZQ. Thus, the search for the presence of components of the autophagy pathway can be used in order to explore the development of new molecular targets against this parasite, through the identification of genes constituent of this pathway in the databases generated by the genomic and transcriptome studies of the parasite. Based on these facts, this work aimed to study the molecular and functional aspects of the autophagy pathway in S. mansoni, through the characterization of the autophagic pathway during the life cycle of the parasite, with the in silico identification of the main components involved; and identification of autophagic vacuoles in couples of adult worms by transmission electron microscopy and fluorescence microscopy after starvation by glucose deprivation. For this purpose, in silico (Blastp- Basic Local Alignment Search Tool - Protein) was performed, using orthological autophagy proteins against the S. mansoni genome, resulting in 21 predicted proteins. Of these, the SmLGG-1, SmUNC-51, SmVPS-34 and SmATG-9 proteins showed significant identity with the LGG-1, UNC-51, VPS-34 and ATG-9 proteins of C. elegans, respectively. The four predicted proteins of S. mansoni present the essential residues for their function evolutionarily conserved, according to the same domains of orthologous. We also construct the phylogenetic tree for these four proteins, comparing them to orthologous proteins, corroborating with the tree of life. For the evaluation of adult worms in nutrient stress conditions, the worms were cultivated in culture medium supplemented with glucose at different concentrations for up to 72 hours, showing subtle changes in their viability, mainly at 72 hours, and a significant change in ovoposition according to decreased glucose concentrations. Finally, after transmission electron microscopy and fluorescence analysis, the presence of acid vacuoles in the lowest glucose concentrations was observed at 72 hous. Accordingly, the methodologies used confirm the existence of the pathway, requiring more details for a better understanding of the parasite biology, being of crucial importance future studies that complement the description of the pathway in S. mansoni.